Elucidation of Photoluminescence Blinking Mechanism and Multiexciton Dynamics in Hybrid Organic–Inorganic Perovskite Quantum Dots. Issue 33 (25th June 2019) - Kim, Taehee; Jung, Seok Il; Ham, Sujin; Chung, Heejae; Kim, Dongho
Abstract: Halide perovskites (ABX3 ) have emerged as promising materials in the past decade owing to their superior photophysical properties, rendering them potential candidates as solar cells, light‐emitting diode displays, and lasing materials. To optimize their utilization into optoelectronic devices, fundamental understanding of the optical behaviors is necessary. To reveal the comprehensive structure–property relationship, CH3 NH3 PbBr3 (MAPbBr3 ) perovskite quantum dots (PQDs) of three different sizes are prepared by controlling the precipitation temperature. Photoluminescence (PL) blinking, a key process that governs the emission efficiency of the PQD materials, is investigated in detail by the time‐resolved spectroscopic measurements of individual dots. The nature of the generated species in the course of blinking events is identified, and the mechanism governing the PL blinking is studied as a function of PQD sizes. Further, the practical applicability of MAPbBr3 PQDs is assessed by studying the multiexciton dynamics under high photoexcitation intensity under which most of the display devices work. Ultrafast transient absorption spectroscopy helped in uncovering the volume‐dependent Auger recombination rates, which are further explored by comparing the early‐time transitions related to surface trap states and higher band states. Abstract : Organic–inorganic hybrid perovskite quantum dots (PQDs) exhibit a size‐dependent trend in photoluminescence (PL) blinking and multiexciton dynamics. The mechanism of PL blinking in individual PQDs is revealed, and the effects of deep, shallow, and higher trap states are discriminated. The Auger recombination in smaller PQD is associated with efficient intraband transition and Auger ionization to the high‐energy trap states.